Survey research - Sapsford, Roger (London : SAGE, 2007)
Presenting an informative and accessible account of survey research, this title guides the reader through the main theoretical and practical aspects of the subject and illustrates the application of survey methods through examples.
Previous ed.: 1999.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social surveys